Fenomena Belajar Membaca Al-Qur’an pada Orang Dewasa: Studi Metode Tilawati Di LPQ Asy-Syafi’iyyah Tanjungtani Nganjuk Jawa Timur - A. Hanafi (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
This article discusses the phenomenon of adults studying the Koran at LPQ Asy-Syafi'iyyah Tanjungtani. LPQ Asy-Syafi'iyyah Tanjungtani Nganjuk is one of the Islamic religious education institutions that guide learning the Koran for adults who have never studied the Koran before. Researchers used qualitative methods with a descriptive analysis approach. In collecting data, the researcher used 3 methods, namely observation, interview, and documentation. This study found that getting closer to Allah is the main motive for adults to learn the Qur'an. However, there are also social motives. Namely, adults still want to hone their abilities to be better in the field of reading the Qur'an. The motive for wanting to be appreciated is that they still want to get appreciation from others because, according to them, people who are proficient in reading the Qur'an will be respected by the community. The last is socializing to fill spare time and friendships with peers.